Korean Peninsula Nuclear Challenges: The Imperative of Regional Cooperative Security Solutions - Huntley, Wade L (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.27 Mongolian Journal of International Affairs No.14 2007 pp.71-87